2021
DOI: 10.1063/5.0054612
|View full text |Cite
|
Sign up to set email alerts
|

Temperature enhanced responsivity and speed in an AlGaN/GaN metal-heterostructure-metal photodetector

Abstract: An AlGaN/GaN metal-heterostructure-metal (MHM) ultraviolet (UV) photodetector employing lateral Schottky contacts was fabricated and characterized at different temperatures. As the temperature increased from 25 to 250 °C, the photoresponsivity of the MHM photodetector increased 3.5 times. This was attributed to the spontaneous-polarization-induced spatial separation of the photogenerated electrons and holes and the increased optical absorption at higher temperatures. Meanwhile, the decay time constant of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The output signals, as exhibited in Figure b–e, for 50 Hz, 100 Hz, 500 Hz, and 1 kHz, were captured at 293 K environment by an oscilloscope (Tektronix MDO34). The obvious elongated recovery time of the photocurrent is known as the persistent photoconductivity (PPC) effect, which is mostly attributed to the numerous defect-induced trap states in the device. , This universally observed PPC effect severely limits the response speed in GaN-based optoelectronic devices. It has been reported that elevated temperatures can accelerate atom migration and therefore promote carrier collection to suppress the PPC effect. ,,, However, it brings drawbacks as an additional heating unit with extra power consumption is required. Fortunately, in this work, arising from the narrow fin width, the drift length of the photocarriers is shortened, and carriers can reach high velocity at a low bias voltage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The output signals, as exhibited in Figure b–e, for 50 Hz, 100 Hz, 500 Hz, and 1 kHz, were captured at 293 K environment by an oscilloscope (Tektronix MDO34). The obvious elongated recovery time of the photocurrent is known as the persistent photoconductivity (PPC) effect, which is mostly attributed to the numerous defect-induced trap states in the device. , This universally observed PPC effect severely limits the response speed in GaN-based optoelectronic devices. It has been reported that elevated temperatures can accelerate atom migration and therefore promote carrier collection to suppress the PPC effect. ,,, However, it brings drawbacks as an additional heating unit with extra power consumption is required. Fortunately, in this work, arising from the narrow fin width, the drift length of the photocarriers is shortened, and carriers can reach high velocity at a low bias voltage.…”
Section: Resultsmentioning
confidence: 99%
“…52−54 It has been reported that elevated temperatures can accelerate atom migration and therefore promote carrier collection to suppress the PPC effect. 15,20,55,56 However, it brings drawbacks as an additional heating unit with extra power consumption is required. Fortunately, in this work, arising from the narrow fin width, the drift length of the photocarriers is shortened, and carriers can reach high velocity at a low bias voltage.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in photocurrent density with increasing the temperature should be associated with the enhanced absorption of AlN at elevated temperature, which in turn leads to the absorption of more photons emitted by the 185 nm lamp. [ 37–40 ] After turning off the light, the device can quickly recover the initial value in the dark state at all temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Since Al x Ga 1-x N ultraviolet (UV) detectors can play an important role in flame warning, biochemical detection, missile tracing, biomedical detection and other areas involving UV detection [ 1 , 2 , 3 ], there has been much research carried out on Al x Ga 1-x N UV photodetectors in recent years. Several studies have been carried out on various types of detectors, such as Schottky barrier [ 4 ], Metal–Semiconductor–Metal (MSM) [ 5 ] and p-i-n [ 6 ] structures. In addition, solar-blind focused plane arrays [ 7 ] have been realized.…”
Section: Introductionmentioning
confidence: 99%